IS IT IMPORTANT FOR ISLAMIC BOARDING SCHOOLS TO HAVE AN ACCOUNTING INFORMATION SYSTEM? - Nurlaily, Liafatra (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Islamic boarding schools, as Islamic educational institutions in Indonesia, play a crucial role in character formation and human resource development. In addition to providing religious education, pesantren also contribute to economic independence through efficient financial management. However, many Islamic boarding schools still use ineffective manual recording methods, hindering financial statement accountability and transparency. This study aims to demonstrate the importance of accounting information systems (AIS) in the financial management of Islamic boarding schools. Literature studies and interviews with pesantren managers found that the current conditions of financial recording and management raise several issues, including the complexity of financial records and the difficulty of knowing the actual balance on each account. As a result, decision-making cannot be carried out promptly and is prone to unwise decisions. The results of the literature show that AIS helps in better financial management and contributes to increasing stakeholder trust in pesantren